Development of Website-Based Tool for Nursing Data Analysis - Hasby Pri Choiruna; Indah Setiawati; Indra Herdiana; Irnanda Naufal Riandi; Indah Ramadhan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background. Historically, nursing data analysis has relied on manual processes guided by individual experience and the Indonesian Nursing Diagnosis Standards (SDKI). This approach often leads to incomplete diagnoses and inefficient validation times. While Hospital Management Information Systems (SIMRS) are currently used for documentation, they lack integrated tools for early-stage diagnostic analysis. Consequently, there is a critical need for online analytical tools that can streamline the application of SDKI standards. Methods. The primary objective of this study is to develop a website-based platform designed to automate the analysis of nursing data. The design of this study is the waterfall method which consists of communication, planning, modeling, construction, and deployment. Results. Findings indicate that the developed website-based platform for nursing data analysis is accessible through the following primary URLs: https://ns.ramut.my.id/layanan/ramut-nursing-data-analysis-rnda or alternative link: https://rnda.ramut.my.id. Conclusion. This website-based tool provides nurses with flexible access to data analysis capabilities, facilitating more efficient and accurate identification of nursing problems in adherence to the Indonesian Nursing Diagnosis Standards (SDKI).